1996
DOI: 10.1074/jbc.271.50.31885
|View full text |Cite
|
Sign up to set email alerts
|

Processing of β-Amyloid Precursor Protein by Cathepsin D

Abstract: The events leading to the formation of ␤-amyloid (␤A4) from its precursor (␤APP) involve proteolytic cleavages that produce the amino and carboxyl termini of ␤A4. The enzyme activities responsible for these cleavages have been termed ␤-and ␥-secretase, respectively, although these protease(s) have not been identified. Since ␤A4 is known to possess heterogeneity at both the amino and carboxyl termini, ␤-and ␥-secretases may actually be a collection of proteolytic activities or perhaps a single proteolytic enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Potentially, a diversity of hydrolases present in saliva can be responsible for this cleavage. Cathepsins, for instance, are known to recognize and cleave a wide range of peptide bonds, among which are Arg-Arg, Lys-Lys, and Phe-Arg (6,10,15,22,30,32,42). As well as the cathepsins, other salivary proteases, like alanine aminopeptidase and dipeptidyl peptidase IV, may play a role in the cleavage of these three substrates (2).…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, a diversity of hydrolases present in saliva can be responsible for this cleavage. Cathepsins, for instance, are known to recognize and cleave a wide range of peptide bonds, among which are Arg-Arg, Lys-Lys, and Phe-Arg (6,10,15,22,30,32,42). As well as the cathepsins, other salivary proteases, like alanine aminopeptidase and dipeptidyl peptidase IV, may play a role in the cleavage of these three substrates (2).…”
Section: Discussionmentioning
confidence: 99%
“…While definitive identification of this fragment will require isolation and amino acid sequencing, it has previously been reported that the activity of cathepsin D is decreased in the blood of AD subjects (Straface et al, 2005). Cathepsin D is an aspartyl protease that cleaves APP at a number of different sites (Higaki et al, 1996), including at Ser627, Phe765, Glu766, and Met768. Cleavage at these sites would give rise to a number of 15 kDa fragments; subsequent -cleavage of these fragments by ␥-secretase at Met722 would give rise to a 10 kDa fragment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also suggested the potential role of cathepsin D in conjunction with cathepsins S and L in degrading the invariant chain and endocytosed antigens within antigen-presenting cells (57). Finally, some properties associated with cathepsin D favor its putative role in the amyloidogenic processing of ␤-amyloid precursor protein within the endo-lysosomal compartment (43,58).…”
Section: Table Imentioning
confidence: 99%